Resource constraints and private sector investment in emerging economies: A review of the literature - Ababio, J.O-M.; Osei, K.A.; Bokpin, G. (University of Ghana, 2015)
This paper is a review and classification of literature on Private Sector Investment in Emerging Economies. Hundred and ten (110) articles published in a broad range of internationally recognized journals covering four major private sector investment (PSI) issues in Emerging Economies (EEs) were explored and analyzed. This paper also reviewed literature on the main segments of private sector investment: domestic investment, foreign direct investment, and international (private) portfolio investment in EEs. A review of the major streams of PSI research examining the determinants, constraints, uncertainties, management and performance as well as relevance and magnitude of PSI activities points out the current gaps and contributions for the growth and survival of private firms and the importance of PSI for economic growth and development in EEs. A unified perspective on these research, identifies and highlights imperative gaps for future research. Consequently, the review will serve as a roadmap indicating the current state, contributions and direction of research topics for the academics and practitioners.
School of social sciences colloquium
Keywords: domestic investment; foreign direct investment; Emerging Economies (EEs); private sector investment (PSI)